Production of slow release crystal fertilizer from wastewaters through struvite crystallization: a review - Md. Mukhlesur Rahman,; Mohd. Salleh, Mohamad Amran; Rashid, Umer; Amimul Ahsan,; Hossain, Mohammad Mujaffar; Ra, Chang Six (King Saud University, 2014)
Nitrogen and phosphorus in wastewaters are a burning environmental issue of the present world. This review covers the studies conducted on the removal and recovery of phosphorus and nitrogen from wastewaters through struvite crystallization. Wastewater which contains a high amount of phosphorus and nitrogen would be a good source of struvite. Struvite is a phosphate fertilizer, although it contains a significant amount of nitrogen and magnesium, and it is an effective alternative source of rock phosphate to maintain the agricultural production system. The present review deals with the principles and concept of struvite nucleation, crystal growth and the factors that affect on the struvite quality. Struvite precipitation occurs in an equimolecular concentration of Mg2+, View the MathML sourceNH4+ and View the MathML sourcePO43− at slightly alkaline conditions. Addition of a source of Mg is essential to maintain the favorable condition of PO4 and Mg. Different factors such as Mg:PO4 molar ratio, pH, aeration rate, reactor types, as well as P and N removal efficiencies were also discussed throughout this review. The slower nutrient leaching loss and its fertilizer quality make struvite an eco-friendly fertilizer. It is possible to overcome the acute shortage of rock phosphate if all the municipal and livestock wastewaters are connected with the wastewater treatment plants.